2017
DOI: 10.1051/0004-6361/201630302
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for small disk-like bulges in a sample of late-type spirals

Abstract: Context. About 20% of low-redshift galaxies are late-type spirals with a small or no bulge component. Although they are the simplest disk galaxies in terms of structure and dynamics, the role of the different physical processes driving their formation and evolution is not yet fully understood. Aims. We investigated whether small bulges of late-type spirals follow the same scaling relations traced by ellipticals and large bulges and if they are disk-like or classical bulges. Methods. We derived the photometric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 107 publications
(157 reference statements)
5
29
0
Order By: Relevance
“…The position of our sample bulges in the FPR, FJR, and KR confirmed the recent findings of Costantin et al (2017) on scaling relations for elliptical galaxies and bulges. They claimed that there is a single population of galaxy spheroids that follow the same FPR (Fig.…”
Section: Galaxysupporting
confidence: 91%
See 3 more Smart Citations
“…The position of our sample bulges in the FPR, FJR, and KR confirmed the recent findings of Costantin et al (2017) on scaling relations for elliptical galaxies and bulges. They claimed that there is a single population of galaxy spheroids that follow the same FPR (Fig.…”
Section: Galaxysupporting
confidence: 91%
“…to separate classical from disk-like bulges. We found that all our bulges are consistent with the magnitude trend highlighted by Nigoche-Netro et al (2008) and Costantin et al (2017), discriminating between less and more massive bulges. As a consequence, using the KR to separate bulge types results in classifying less massive bulges as disk like.…”
Section: Scaling Relationssupporting
confidence: 85%
See 2 more Smart Citations
“…Intrinsic shapes of bulges have been extensively investigated by Méndez-Abreu et al (2008, Costantin et al (2017Costantin et al ( , 2018, and de Lorenzo-Cáceres et al (2019). Without constraints from stellar kinematics, however, it is extremely difficult to measure the intrinsic shapes of individual bulges.…”
Section: Bulge Dichotomy In Their Intrinsic Shapesmentioning
confidence: 99%